2022
DOI: 10.1002/aur.2686
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of abnormalities in limbic networks of autism spectrum disorder children: Evidence from an autism spectrum disorder twin study

Abstract: Although the limbic system is closely related to emotion and social behaviors, little is known about the integrity of limbic pathways and how genetics influence the anatomical abnormalities of limbic networks in children with autism spectrum disorder (ASD). Therefore, we used an ASD twin study design to evaluate the microstructural integrity and autism-related differences in limbic pathways of young children with ASD and to estimate the heritability of limbic tracts microstructure variance. We obtained diffusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 71 publications
0
1
0
Order By: Relevance
“…Research has confirmed that limbic regions such as the amygdala and hippocampus are functionally related to impaired abilities in ASD, which are correlated with repetitive and stereotyped behavior (Fu et al, 2022 ; Nees et al, 2022 ; Thabault et al, 2022 ). Our results showed that the limbic gray value in the ASD group was lower than that in the adult HC group.…”
Section: Discussionmentioning
confidence: 96%
“…Research has confirmed that limbic regions such as the amygdala and hippocampus are functionally related to impaired abilities in ASD, which are correlated with repetitive and stereotyped behavior (Fu et al, 2022 ; Nees et al, 2022 ; Thabault et al, 2022 ). Our results showed that the limbic gray value in the ASD group was lower than that in the adult HC group.…”
Section: Discussionmentioning
confidence: 96%
“…A higher FA in the corpus callosum is associated with impaired social and communicative functions, and that in the inferior longitudinal fasciculus and inferior fronto-occipital fasciculus is associated with difficulty in recognizing emotions and facial expressions [11,59]. During the childhood phase in ASD individuals, there is a decline in FA, primarily observed in the sagittal stratum, corpus callosum, superior cerebellar peduncle, superior longitudinal fasciculus, cingulum, and uncinate fasciculus, which are associated with motor functions, language, and social impairments [57,58,[60][61][62][63][64][65]. However, Weinstein et al [66] found increased FA values in the corpus callosum and superior longitudinal fasciculus in children with ASD aged 1.5-6 years old.…”
Section: Studying Brain Network Changes In Children With Asd Using Dtimentioning
confidence: 99%
“…When the child gets involve in more of the sensory stimulus during play the connectivity between neuron not only increases but get richer in information and its processing. Thus sensory processing is one of the major requirements to intricate learning, creativity and imagining among children 10 . Sensory integration by the Ayres signifies to the capability to produce suitable motor and behavioral responses to stimuli.…”
Section: Introductionmentioning
confidence: 99%